(untitled) (London, 2003)
This volume consists of papers delivered at the International Mathematica Symposium 2003 — an interdisciplinary meeting bringing together users of Mathematica in research and education. It gathers research papers, reports on classroom practice, reports on the use of Mathematica in industry and commerce, and descriptions of fresh applications.
Keywords: Mathematical statistics,Toán thống kê